Application of 3D-printed porous prosthesis for the reconstruction of infectious bone defect with concomitant severe soft tissue lesion: a case series of 13 cases - Zhuo Chen; Yiyuan Yang; Bingchuan Liu; Xingcai Li; Yun Tian (BMC Musculoskeletal Disorders)
Abstract Background Treating infectious bone defects combined with large soft-tissue lesions poses significant clinical challenges. Herein, we introduced a modified two-stage treatment approach involving the implantation of 3D-printed prostheses and flap repair to treat large segmental infectious tibial bone defects. Method We conducted a retrospective study of 13 patients treated at our center between April 2018 and March 2022 for tibial infections owing to posttraumatic infection and chronic osteomyelitis combined with soft tissue defects. The average defect length was 14.0 cm (range, 5.7–22.9 cm). The flap area ranged from 14 × 5 to 15 × 8 + 25 × 15 cm. Sural neurocutaneous, lesser saphenous neurocutaneous, and local fasciocutaneous flaps were used to repair the skin defects. In the second stage, 3D-printed prostheses were designed and implanted. Union rate, complications, and functional outcomes were assessed at the final follow-up. Result The average follow-up period was 31.1 months (range, 17–47 months), with an average interval of 208.1 days (range, 139–359 days) between the two stages. According to our criteria, 7 of the 13 patients achieved radiographic healing without intervention. Two patients developed prosthesis-related complications and underwent revision surgery. Two patients experienced recurrent infections leading to prosthesis removal and debridement surgery, with the infection ultimately eradicated in one and the other undergoing amputation. Three patients experienced noninfectious flap-related complications, however, all eventually healed through surgical intervention. Conclusion The use of 3D-printed porous titanium prostheses combined with flap soft-tissue repair for the treatment of infectious tibial bone defects did not increase the rate of infection recurrence and provided good functional recovery, offering more options for the treatment of infectious bone defects.